Lysine-specific demethylase 1 regulates hematopoietic stem cell expansion and myeloid cell differentiation - Staehle, Hans Felix; Koellerer, Christoph; Staehle, Anne Marie; Schulze, Jana; Eble, Philipp; Müller, Anja; Zell, Franziska; Müller, Judith M.; Perner, Florian; Attia, Aya; Mallm, Jan-Philipp; Pozdnyakova, Olga; et al. (Cell death & disease, 2025)
The lysine-specific demethylase 1 (LSD1) regulates hematopoietic stem cell differentiation and has been identified as a therapeutic target in hematological disorders. LSD1 demethylates mono and dimethylated histones 3 at lysine 4 and 9. In addition, it acts as a scaffold for the formation of chromatin-modifying complexes that regulates the transcription of myeloid-lineage-specific genes in complex with GFI1, a transcriptional repressor. While both enzymatic and non-enzymatic functions of LSD1 have been well defined, the relative importance of these two functions in hematopoiesis remains incompletely understood. Here, we investigated the contribution of enzymatic and non-enzymatic functions of LSD1 to myelopoiesis. We show that myeloid differentiation is independent of the enzymatic functions of LSD1 but requires the non-enzymatic, scaffolding function, which directs GFI1 binding to target sequences. In the absence of the LSD1 protein, GFI1 DNA binding is diminished, and myeloid cell differentiation arrests at an immature, myelomonocytic-like cell stage, which overexpresses Prtn3. We provide functional data implicating Prtn3 as an effector of the stem cell expansion and myeloid maturation block caused by the loss of LSD1.
Online veröffentlicht: 15. August 2025
Gesehen am 20.01.2026